Mindfulness: An Introduction - Parth Naik; Victor Harris; Larry Forthun (EDIS, 2013)
Learning to be mindful is a powerful skill that can help you face the stresses of day-to-day life and improve both your psychological and physical health. Because you don’t need any equipment to practice mindfulness, you can practice it discreetly anywhere, at any time. This 6-page fact sheet was written by Parth Naik, Victor Harris, and Larry Forthun, and published by the UF Department of Family Youth and Community Sciences, September 2013.